2010
DOI: 10.1007/s10654-010-9435-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and the risk of cardiovascular diseases

Abstract: Previous large epidemiological studies reporting on the association between chronic obstructive pulmonary disease (COPD) and cardiovascular diseases mainly focussed on prevalent diseases rather than on the incidence of newly diagnosed cardiovascular outcomes. We used the UK-based General Practice Research Database (GPRD) to assess the prevalence and incidence of cardiovascular diseases in COPD patients aged 40-79 between 1995 and 2005, and we randomly matched COPD-free comparison patients to COPD patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 33 publications
9
114
2
2
Order By: Relevance
“…In other studies of lung function and stroke, [15,14,23,22] or COPD and stroke, [16,19] estimates were only reduced with around 10%…”
Section: Methodological Considerationsmentioning
confidence: 87%
See 4 more Smart Citations
“…In other studies of lung function and stroke, [15,14,23,22] or COPD and stroke, [16,19] estimates were only reduced with around 10%…”
Section: Methodological Considerationsmentioning
confidence: 87%
“…[16] The incidence of stroke subtypes in COPD has not previously been assessed, to our knowledge. Studies of lung function in the general population have, however, reported inverse relationships of FEV1 with incidence of IS [15,22,23] and SAH [9], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations